2002
DOI: 10.1162/089892902320474508
|View full text |Cite
|
Sign up to set email alerts
|

Models of Functional Organization of the Lateral Prefrontal Cortex in Verbal Working Memory: Evidence in Favor of the Process Model

Abstract: Research on the functional organization of the lateral prefrontal cortex (PFC) in working memory continues to be fairly equivocal between two major frameworks: organization-by-process or organization-by-material. Although there is fairly strong evidence for organization-by-process models from event-related fMRI studies, some investigators argue that the nature of the stimulus material better defines the functional organization of the lateral PFC, particularly in more ventral regions (BA 47/45/44). Specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 28 publications
7
55
2
1
Order By: Relevance
“…Our findings are consistent with several studies that reported increased DLPFC activation during "manipulation" tasks that required participants to modify the sequential relationships among items that are currently active in WM Wagner et al, 2001b;Barde and Thompson-Schill, 2002). DLPFC activation has also been reported in studies investigating "chunking," which involves processing of relationships to build higher-level groupings among items that are active in WM (Bor et al, 2004).…”
Section: Dlpfc and Wm Processingsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings are consistent with several studies that reported increased DLPFC activation during "manipulation" tasks that required participants to modify the sequential relationships among items that are currently active in WM Wagner et al, 2001b;Barde and Thompson-Schill, 2002). DLPFC activation has also been reported in studies investigating "chunking," which involves processing of relationships to build higher-level groupings among items that are active in WM (Bor et al, 2004).…”
Section: Dlpfc and Wm Processingsupporting
confidence: 91%
“…Several neuroimaging studies have implicated the left VLPFC in linguistic control processes (Wagner et al, 2001a;Barde and Thompson-Schill, 2002;Gold and Buckner, 2002). According to one account (Poldrack et al, 1999;Wagner et al, 2001a), the left aVLPFC (BA 45 and 47) implements controlled retrieval and maintenance of semantic information, whereas the left pVLPFC (BA 6 and 44) implements controlled retrieval and maintenance of phonological information [for alternative viewpoints, see Barde and Thompson-Schill (2002) and Gold and Buckner (2002)].…”
Section: Vlpfc Subregions Involved In Encodingmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the frontal and parietal regions activated by the naming task showed this general sensitivity to time on task regardless of the particular reading condition. Many of these areas, including the IFG bilaterally, left precentral sulcus, and IPS, have been linked in prior studies to working memory processes (e.g., Barde and Thompson-Schill, 2002 LaBar et al, 1999;Paulesu et al, 1993;Smith et al, 1998;Wager and Smith, 2003). Others, including the FEF, anterior cingulate gyrus, and IPS, are the principal components of a well-described frontoparietal attention network (e.g., Adler et al, 2001;Corbetta and Shulman, 2002;Gitelman et al, 1999;Kastner and Ungerleider, 2000;LaBar et al, 1999;Mesulam, 1999;Yantis et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…This three-component model applies to several types of verbal materials, including letters (e.g., Awh et al, 1996;Cohen et al, 1994;Schumacher et al, 1996), digits (Petrides et al, 1993), pseudowords (Barde and Thompson-Schill, 2002), and words (Clark et al, 2000;Crosson et al, 1999). However, it is not known whether WM in second language (L2) involves this cognitive -neural system.…”
Section: Introductionmentioning
confidence: 99%